Ischemic-LTP in Striatal Spiny Neurons of both Direct and Indirect Pathway Requires the Activation of D1-Like Receptors and NO/Soluble Guanylate Cyclase/cGMP Transmission. Issue 2 (February 2013) - Arcangeli, Sara; Tozzi, Alessandro; Tantucci, Michela; Spaccatini, Cristiano; de Iure, Antonio; Costa, Cinzia; Filippo, Massimiliano Di; Picconi, Barbara; Giampà, Carmen; Fusco, Francesca Romana; Amoroso, Salvatore; Calabresi, Paolo
Striatal medium-sized spiny neurons (MSNs) are highly vulnerable to ischemia. A brief ischemic insult, produced by oxygen and glucose deprivation (OGD), can induce ischemic long-term potentiation (i-LTP) of corticostriatal excitatory postsynaptic response. Since nitric oxide (NO) is involved in the pathophysiology of brain ischemia and the dopamine D1/D5-receptors (D1-like-R) are expressed in striatal NOS-positive interneurons, we hypothesized a relation between NOS-positive interneurons and striatal i-LTP, involving D1R activation and NO production. We investigated the mechanisms involved in i-LTP induced by OGD in corticostriatal slices and found that the D1-like-R antagonist SCH-23390 prevented i-LTP in all recorded MSNs. Immunofluorescence analysis confirmed the induction of i-LTP in both substance P-positive, (putative D1R-expressing) and adenosine A2A-receptor-positive (putative D2R-expressing) MSNs. Furthermore, i-LTP was dependent on a NOS/cGMP pathway since pharmacological blockade of NOS, guanylate-cyclase, or PKG prevented i-LTP. However, these compounds failed to prevent i-LTP in the presence of a NO donor or cGMP analog, respectively. Interestingly, the D1-like-R antagonism failed to prevent i-LTP when intracellular cGMP was pharmacologically increased. We propose that NO, produced by striatal NOS-positive interneurons via the stimulation of D1-like-R located on these cells, is critical for i-LTP induction in the entire population of MSNs involving a cGMP-dependent pathway.